Kinetic evaluation of photocatalytic decoloration of Synozol Red K3BS dye using TiO2-anatase and direct solar radiation - Ramírez Revilla, Stamber Álvaro (2023)
The intense solar radiation of the city of Arequipa has been used as an activation factor for TiO2 anatase to evaluate the decoloration kinetics of the Synozol Red K3BS textile dye. For this purpose, a factorial design (23) was developed to optimize reaction time values, pH and TiO2 doses for 200 mL of solution. The optimal factors for the study were: a 60 min duration, a pH of 3 and 0.1 g of photocatalyst. The first-order kinetic model adequately explained the decoloration of a solution at a concentration of 40 mg/L, showing an excellent reaction rate constant (k=0.0333 min-1) and a decoloration percentage of 86.15%